PERWALIAN ANAK BIL MA’I SUBHAH;KAJIAN TERHADAP PUTUSAN PENOLAKAN ISBAT NIKAH - Khoirul Ahyar (Nizham Jurnal Studi Keislaman, 2021)
Controversy over marital status failed in marriage is common in society. Does not cover the possibility of the validity of the marriage is null and void, and the father may lose custody. So how about the guardianship of marriage from the parents whose marriage is denied by the religious court While they are actually married couples. As an effort to break it down, it is by detailing the condition of the child out of wedlock from the marriage that is rejected by the marriage contract as well as the integration of the applicable laws and regulations. And it is also known that the Penghulu who set the guardian of the marriage has the flexibility to testify based on Islamic law and population data as stated in PMA number 20 of 2019. So this research is conducted to obtain data that has been tested its scientific truth, find the source of the problem of failure in marriage. The conclusion of this study is that the couple whose marriage was rejected by the religious court is included in the category of subhah marriage which according to fuqoha does not cause the annulment of the previous marriage. Therefore, one should be careful not to think that the accusation of adultery for a person whose marriage is rejected is rejected by the religious court as the views of fuqoha and scholarly agreement.